The disease of corruption: views on how to fight corruption to advance 21st century global health goals. Issue 1 (December 2016) - Mackey, Tim; Kohler, Jillian; Savedoff, William; Vogl, Frank; Lewis, Maureen; Sale, James; Michaud, Joshua; Vian, Taryn
Abstract Corruption has been described as a disease. When corruption infiltrates global health, it can be particularly devastating, threatening hard gained improvements in human and economic development, international security, and population health. Yet, the multifaceted and complex nature of global health corruption makes it extremely difficult to tackle, despite its enormous costs, which have been estimated in the billions of dollars. In this forum article, we asked anti-corruption experts to identify key priority areas that urgently need global attention in order to advance the fight against global health corruption. The views shared by this multidisciplinary group of contributors reveal several fundamental challenges and allow us to explore potential solutions to address the unique risks posed by health-related corruption. Collectively, these perspectives also provide a roadmap that can be used in support of global health anti-corruption efforts in the post-2015 development agenda.